Brain anatomy and functional differences in developmental stuttering - Chang, Soo-Eun (Henry Stewart Talks, 2017)
Stuttering as a neurodevelopmental disorder, Neural mechanisms and theoretical models of fluent speech, Neuroimaging methods used to study speech and language, Convergent evidence on the neural bases of stuttering, Brain structural and functional differences in children who stutter, Future research: the neural mechanisms behind stuttering onset, persistence, and recovery during childhood